Enhancing management accounting practice through Islamic values: a case study of a Malaysian Islamic bank / Mohd Haniff Zainuldin, Ibrahim Kamal Abdul Rahman and Mohd Nizal Haniff - Zainuldin, Mohd Haniff; Abdul Rahman, Ibrahim Kamal; Haniff, Mohd Nizal (Faculty of Accountancy, 2013)
This is a concept paper discussing how certain Islamic principles are infused into the overall management accounting practices of an Islamic Bank which was incorporated in Malaysia. The Bank has successfully integrated these principles in its management system and in turn has created a unique approach to management accounting practices for an Islamic Financial Institution (IFI). This approach earned the Bank, the prestigious National Award for Management Accounting (NAfMA) in 2008for the best practice solutions award category in recognition of the Bank's effective applications of management accounting system and tools that has had a positive impact of daily practice. This paper discusses the strategies employed by the Bank and its application of Islamic values.